Субпіксельна обробка зображень у системах моніторингу видимого діапазону хвиль - Фабіровський, С. Є. (Видавництво Львівської політехніки, 2014)
Наведено аналіз методів підвищення роздільної здатності, технології субпіксельної обробки зображень, оцінка варіантів побудови оптичних систем. У межах роботи проаналізовано шляхи підвищення роздільної здатності, вказано переваги та недоліки методів. TThis paper is devoted to considering of ways to improve the resolution, principles and methods of subpixel imaging technology, assessment of the development status and the latest research developments. Modern approaches to improving the spatial resolution as the main parameter of satellite images are based on algorithmic search and design solutions as the technology of manufacturing image sensors exhaust its potential for improvement. One of the major tasks of remote monitoring is to improve the quality of images, which is determined by parameters such as resolution. Resolution of digital images, in its turn, is determined by the number of pixels of which it is composed. The need for high resolution usually is accompanied by the need to capture the largest possible surface area. However, reducing the pixel size and increasing their number is limited by technological factors and is associated with difficulties of the operation and handling. Pixel size of CCD is technology limited. Increasing of pixels number and hence the resolution will increase the size (length) of CCD line. As the result, there is need to use more expensive optics, weight of which is greater or reduce the focal length of the optical system. The solution to this situation is the use of subpixel processing. The advantages of subpixel imaging include the possibility to increase the spatial resolution without changing the optical system. The essence of the subpixel processing is constructive two CCD lines shifted by half a pixel with respect to each other. Use of subpixel imaging technology allows to increase the resolution of the instrument, or, in case of saving a lower resolution, to reduce the focal length of the system and reduce the weight and volume of the optical system, which is crucial for monitoring systems. During subpixel imaging, there are high requirements to the board processor, memory and bandwidth of the radio frequency channel of system. The need to increase the resolution a monitoring systems helps to find new, more effective, methods to increase resolution. The paper analyzes ways of increasing resolution the advantages and disadvantages of existing techniques are analyzed. The scope of subpixel processing methods in existing monitoring systems of visible wavelength range is considered. The need to further improvement monitoring systems resolution helps to find new, more effective methods of signal processing and filtering. The studied modern methods of subpixel image processing effectively increase the resolution. Thus, based on the analysis, we can conclude that increasing the system resolution should be conducted by subpixel processing methods that require improvement.
Subpixel image processing in monitoring systems of visible wavelengths
Keywords: обробка зображень; субпіксельна обробка зображень; просторова роздільна здатність; оптичний давач; інтерполяція; деконволюція; відновлення; ПЗЗ лінійка; інтерполяція; деконволюція; відновлення; дистанційне зондування Землі; аерокосмічне знімання; image processing; subpixel image processing; spatial resolution; optical sensor; CCD line; interpolation; deconvolution; remote sensing of the Earth; restoration